On selecting the better of two binomial populations - Mikalauskas, Kęstutis; Eidukevičius, Rimantas (Lietuvos matematikos rinkinys, 2008)
A new procedure for selecting the better of two binomial populations by using sequential analysis proposed. It is based on well known Play-the-Winner(PW) and Vector-at-a Time (VT) procedures and constructed to avoid some disadvantages of PW and VT rules.